Physician's global assessment of disease activity in juvenile idiopathic arthritis: consensus-based recommendations from an international task force - Rypdal, Veronika; Brunner, Hermine I; Feldman, Brian M; Ruperto, Nicolino; Aggarwal, Amita; Angeles-Han, Sheila T; Backström, Maria; Balay-Dustrude, Erin; Bracaglia, Claudia; De Benedetti, Fabrizio; Doležalová, Pavla; Garrone, Marco; et al. (Annals of the rheumatic diseases, 2025)
OBJECTIVES: To develop consensus-based recommendations for physician's global assessment of disease activity (PhGA) scoring and to standardise definitions of disease activity. METHODS: An international task force of 34 members was assembled, and recommendations were developed in 3 phases: (1) 2 preliminary surveys of paediatric rheumatologists and a literature review; (2) 14 videoconference meetings, informed by multicriteria decision analysis and formal anonymous voting; and (3) a 2-day in-person consensus conference using structured nominal group technique discussions and formal voting. The threshold for achieving consensus was ≥78% of voting task force members. Agreement with the final statements was rated using a numerical rating scale from 0, strongly disagree, to 10, strongly agree. RESULTS: Eighteen points to consider were agreed upon. All statements achieved consensus (≥78%), with a level of agreement ≥9.2. Points included the definition of disease activity in juvenile idiopathic arthritis (JIA), factors to assess in nonsystemic JIA and systemic JIA, consideration of available imaging and laboratory tests, the role of extra-articular manifestations, the evaluation of treatment, and the timing of PhGA scoring. CONCLUSIONS: The task force developed consensus-based recommendations when scoring the PhGA in nonsystemic and systemic JIA. These recommendations will lead to more reliable scoring of disease activity in patients with JIA.
Keywords: Rheumatology; Severity of Illness Index; dítě; juvenilní artritida; Consensus; lidé; Advisory Committees; Child; Humans; Arthritis, Juvenile; poradní výbory; konsensus; revmatologie; stupeň závažnosti nemoci